2022
DOI: 10.1021/acs.jpcb.2c01387
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl-Engineered Dual-State Luminogens with Pronounced Odd–Even Effects: Quantum Yields with up to 48% Difference and Crystallochromy with up to 22 nm Difference

Abstract: Alkyl chain-resulted odd–even effects in fluorescence quantum yield (FLQY) have also been reported in organic luminescent materials (OLMs). However, the odd–even effects in FLQY caused by the alkyl substitutes in OLMs are generally very weak, with only single-digit differences. Here, we report a series of alkyl-substituted dual-state luminogens (DSEgens) showing extremely high solid-state FLQY in even-numbered analogues (>90% FLQY) and a dramatically pronounced odd–even effect in FLQY. The odd–even effect in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Previous studies indicate that changes in the nonconjugated side chains pose negeligible influence on system conjugation in the solution state but can influence the 3D packing in the solid state. [24] Therefore, the much weaker solid-state emission of L2 in comparision with that of L1 and L3 could be attributed to the nonradiative pathways enabled by its stronger intermolecular hydrogen bonding by the hydroxyl group on the side chain. The experimental study and theoretical investigation collectively indicate that subtle changes in the side chains without changing the π conjugation could serve as a useful toolbox to tune the photophysical properties of fluorophores in the aggregate state, which has received wide attention in the engineering of DSEgens.…”
Section: Photophysical Propertiesmentioning
confidence: 97%
“…Previous studies indicate that changes in the nonconjugated side chains pose negeligible influence on system conjugation in the solution state but can influence the 3D packing in the solid state. [24] Therefore, the much weaker solid-state emission of L2 in comparision with that of L1 and L3 could be attributed to the nonradiative pathways enabled by its stronger intermolecular hydrogen bonding by the hydroxyl group on the side chain. The experimental study and theoretical investigation collectively indicate that subtle changes in the side chains without changing the π conjugation could serve as a useful toolbox to tune the photophysical properties of fluorophores in the aggregate state, which has received wide attention in the engineering of DSEgens.…”
Section: Photophysical Propertiesmentioning
confidence: 97%
“…Both compounds were synthesized through multi-step reactions (Scheme S1 †) and characterized by 1 H/ 13 C NMR and high-resolution mass spectrometry (Fig. S1-S8 †).…”
Section: Photophysical Properties and Theoretical Calculationsmentioning
confidence: 99%
“…In contrast, solid-state luminescence enhancement (SLE) materials are non-luminescent in solution, but show strong fluorescence in solid/frozen states, 6,8,9 providing new insight into developing highly efficient solid-state luminescent materials. 10 In recent years, there has been a great deal of interest in developing dual-state emission fluorogens (DSEgens) with highly efficient emissions both in solution and the solid state, [11][12][13][14][15] which combine the advantages of TCQ and SLE materials and expand the range of applications. [16][17][18] Early studies have shown that changes in the electronic structures and/or spatial volume of substituents on a fluorophore can exert a significant impact on its solution and solid-state photophysical properties, as proved effective when synthesizing solution and solid-state fluorophores.…”
Section: Introductionmentioning
confidence: 99%
“…38 Despite the progress in achieving DSE proprieties using TPA as a building block, attaining DSE luminogens (DSEgens) with intense emissions remains challenging to researchers. 25,26,28,[39][40][41][42][43][44] One of the key challenges is how to maintain a sufficient ICT process within the twisting molecular conformations.…”
Section: Introductionmentioning
confidence: 99%